Epibionts on Aequipecten tehuelchus (d'Orbigny, 1846) (Pectinidae) in shelf waters off Buenos Aires, Argentina - Souto, Valeria Soledad; Schejter, Laura; Bremec, Claudia Silvia (American Malacological Bulletin)
Aequipecten tehuelchus (d'Orbigny, 1846) is a commercial resource, distributed from Rio de Janeiro (Brazil) to Golfo Nuevo (Argentina), on sandy and muddy bottoms. In Argentina, the major banks of exploitation are located in the gulfs of San José and San Matías. This study represents the first ecological study of A. tehuelchus in shelf waters off Buenos Aires, Argentina. Eighteen epibiont taxa were registered on the individuals analyzed. Polychaetes were the most frequent epibiotic organisms (82%), including Serpulidae (Rafinesque, 1815), Phyllochaetopterus socialis (Claparède, 1869), Idanthyrsus armatus (Kingberg, 1807) and Chaetopterus antarcticus (Kingberg, 1866). Ostrea puelcheana (d'Orbigny, 1842), Balanus cf. amphitrite (Darwin, 1854) and solitary ascidians were found on less than 30% of the sampled individuals. Bryozoa and Porifera were scarcely represented. Phyllochaetopterus socialis, I. armatus and Balanus cf. amphitrite were most frequent on the upper (left) valve. This study nearly doubles the number of epibionts identified and mentioned on A. tehuelchus in Patagonian Gulfs. Three individuals of the commensal pea crab Tumidotheres maculatus (Say, 1818) were found inside three different specimens of A. tehuelchus. One left scallop valve was burrowed into by the parasitic polychaete Polydora (Bosc, 1802). Fil: Souto, Valeria Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Subsede Instituto Nacional de Investigación y Desarrollo Pesquero; Argentina Fil: Schejter, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Subsede Instituto Nacional de Investigación y Desarrollo Pesquero; Argentina Fil: Bremec, Claudia Silvia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Subsede ...